ETHICS BY DESIGN AND RECONSIDERATION OF THE SUBJECT-OBJECT IN THE DIGITAL ERA - Тетяна ПАВЛОВА; Роман ПАВЛОВ (Епістемологічні дослідження у філософії, соціальних і політичних науках)
Purpose: Development of conceptual foundations of ethics by design and rethinking of subject-object relations in the context of digital ethics for the formation of more effective approaches to the design and management of ethically responsible technologies. Design / Method / Approach: The research is based on an interdisciplinary approach combining methods of philosophical analysis, ethics, sociology of technology and research in the field of human-computer interaction. The methods of conceptual modeling, ethical analysis of technologies and scenario forecasting are used. Findings: Considered approaches to the formation of a conceptual model of distributed ethical responsibility in complex sociotechnical systems. Proposed methodological approaches to the integration of ethical considerations at various stages of the life cycle of digital products. The potential of the ethics of care to solve the problems of vulnerability and dependence in the digital environment is investigated. Theoretical implications: The work contributes to the development of the theory of technology ethics, offering a new perspective on the interaction between ethical principles and the processes of designing digital systems. The research expands the understanding of subject-object relations in the context of modern technologies. Practical implications: The proposed approaches can be used to create methodologies for the ethical design of digital products, the formation of policies for the responsible use of technologies in organizations, and the development of educational programs on the ethics of technologies for engineers and designers. Originality / Value: The novelty of the research lies in the development of an integrative approach to ethics by design that takes into account changes in subject-object relations in the digital age. The proposed approach is aimed at expanding the capabilities of existing models of ethical design and explores new perspectives for creating ethically responsible digital technologies. Research limitations / Future research: Prospects include empirical testing of proposed models, development of specific tools for ethical audit of digital systems, and research into cultural aspects of the perception of ethics by design . The limitations are related to the rapid development of technologies, which may require constant adaptation of the proposed approaches. Paper type: Theoretical.